2017
DOI: 10.1016/j.soard.2017.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and other substance use after bariatric surgery: prospective evidence from a U.S. multicenter cohort study

Abstract: Background Empirical evidence suggests Roux-en-Y gastric bypass (RYGB) increases risk of developing alcohol use disorder (AUD). However, prospective assessment of substance use disorders (SUD) following bariatric surgery is limited. Objective To report SUD-related outcomes following RYGB and laparoscopic adjustable gastric banding (LAGB). To identify factors associated with incident SUD-related outcomes. Setting Ten US hospitals. Methods The Longitudinal Assessment of Bariatric Surgery-2 is an observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
156
2
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 225 publications
(194 citation statements)
references
References 27 publications
10
156
2
7
Order By: Relevance
“…Most factors related to substance use disorder that were examined (i.e., sex, age, income, social support, depressive symptoms, mental quality of life, psychiatric hospitalization, antidepressant medication, smoking, alcohol consumption, illicit drug use and surgical procedure(7;25)) were not related to continued or post-surgery initiated opioid use. An exception was that continued benzodiazepine use, which may be suggestive of addictive behavior(36) and increase risk of opioid overdose(37), was associated with an increased risk of continued opioid use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most factors related to substance use disorder that were examined (i.e., sex, age, income, social support, depressive symptoms, mental quality of life, psychiatric hospitalization, antidepressant medication, smoking, alcohol consumption, illicit drug use and surgical procedure(7;25)) were not related to continued or post-surgery initiated opioid use. An exception was that continued benzodiazepine use, which may be suggestive of addictive behavior(36) and increase risk of opioid overdose(37), was associated with an increased risk of continued opioid use.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographics, psychiatric hospitalizations, binge eating, loss of control eating, substance use (smoking, alcohol intake, symptoms of alcohol use disorder and illicit drug use), back, hip, knee and ankle surgeries, and subsequent bariatric procedures (i.e. revisions, reversals, new procedures) were determined with study-specific forms (23;24;25). The Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) assessed physical and mental health(26), with scores transformed to a mean of 50 and standard deviation of 10 in the general U.S. population(27); a lower score indicates worse function.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, reduced alcohol tolerability is considered a complication from bariatric surgery, and empirical evidence indicates that gastric bypass increases the risk of developing both alcohol use disorders and substance use disorders [5, 6]. One study showed that alcohol use disorder more than doubled from 7% prior to surgery to 16% 7 years after surgery [5]. …”
Section: Introductionmentioning
confidence: 99%
“…(3) Furthermore, a subgroup of individuals develop de novo AUDs (3.5–7.0%) (46) and non-alcohol substance use disorders (SUDs). (7) Moreover, many bariatric surgery centers instruct their patients to avoid alcohol after surgery, (8) although prior research suggests most patients with pre-surgery alcohol use problems report continued problematic alcohol use following surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Extant evidence suggests that the RYGB procedure, male sex, younger age, preoperative AUDs or regular alcohol use, and preoperative drug use are associated with postoperative AUDs. (3) While evidence has been somewhat inconsistent, other research found depression, dysregulated eating (i.e., preoperative food addiction, postoperative nocturnal eating, subjective hunger), family history of substance abuse, poor coping, life stressors, and poorer quality of life were related to initiation of substance use post-surgery, (7) with some findings being specific to RYGB patients. (13) …”
Section: Introductionmentioning
confidence: 99%